Measuring and maintaining consistency: A hybrid FTF algorithm - Bunch, James R.; Le Borne, Richard C.; Proudler, Ian K. (Zielona Góra: Uniwersytet Zielonogórski)
Due to the versatility as well as its ease of implementation, the Fast Transversal Filters algorithm is attractive for many adaptive filtering applications. However, it is not widely used because of its undesirable tendency to diverge when operating in finite precision arithmetic. To compensate, modifications to the algorithm have been introduced that are either occasional (performed when a predefined condition(s) is violated) or structured as part of the normal update iteration.
Keywords: FTF; numerical stability; consistency